Afectaciones psicológicas y emocionales en cuidadores primarios de personas postradas en cama de Roldanillo Valle (2021)
The purpose of this research is to know the psychological and emotional affectations in primary caregivers of bedridden people, since this population indicates various psychological and care needs as a consequence of the exhaustion to which they are exposed when caring for a relative with health limitations; based on the general theory of systems. The implemented methodology was qualitative, obtaining information from the Zarit questionnaire and a semi-structured interview that investigated personal, family, work, social and economic aspects. Concluding that people who are dedicated to the care of a bedridden relative usually present symptoms of overload, greater lability in female caregivers and with mother-child bonds. Likewise, it is observed that being linked to work and being male can be factors that reduce the appearance of physical and emotional exhaustion.